Feasibility Study of Construction Additional Production Lines on Jelly Drink Plant at PT XYZ - Sarah Fauzia S. Puspita; Rizal Syarief; Dudi S. Hendrawan (International Journal of Engineering and Management Research, 2020)
Demand forecasting is the first step for production planning and control to fulfil market demand. In line with economic growth in Indonesia, number of jelly drink's sale PT XYZ also increasing especially in 2011-2013 period. Unfortunately, PT XYZ has an issue to fulfil its demand in eastern area, and increasing production is one of solution to solve it. This research aims to analyze market demand of jelly drink in eastern area for the next five years, select the optimal location in which plant production capacity need to be increased and feasibility study of construction additional production lines. Winter's additive time series method is used to analyze market demand and Comparative Performance Index (CPI) method is used to select the location for jelly drink's plant. Net Present Value (NPV), Internal Rate of Return (IRR), and Pay Back Period (PBP) are the parameter for financial aspect on this research. Demand forecasting shows increasing in market demand on 2014-2018 period with 16% MAPE value. The optimum location to increase its production lines is Sidoarjo Plant, East Java. Two production lines can be added with increasing 24.3 million cartoon per year of production. Production aspect, human resources and financial parameter shows that this project is economically justified to execute.